Analisis Dampak Penerapan Manajemen NMtu ISO 9001:2008 terhadap Kualitas Pelayanan Akademik Perguruan Tinggi di Bandar Lampung - Muhammad Rafiq; Aswin - (Jurnal Bisnis Darmajaya, 2015)
The research aims to determine the influence of management implementation of Quality Management System ISO 9001:2008 the college in Bandar Lampung and important aspect of service quality. The samples are all of students of  the colleges was applied quality management system. This study uses regression analysis to determine the impact of academic service quality of the education institutions . Then uses the Cartesian diagram to identify the aspects that are priorities for student academic services related college.The results showed that the significance level 0.034 alpha is smaller than 0.05. It is mean that Ho is rejected and Ha accepted, and it can be stated that the application of ISO 9001:2008 Quality Management System significantly affect the quality of Academic Services . R square of 0.023 or 2.3 % indicates the magnitude of the effect of the application of ISO 9001:2008 Quality Management System on the Quality of Academic Services is still smaller . Based on result of the analysis and then the Cartesian diagram proves that the aspects that determine of the academic services quality and  satisfaction factors are the comfort of the services, facilities services, the attention of service personnel, and personnel responsiveness to student complaints. Keywords : quality management system, quality of service